Two new species of the ant-like spider genus Fluda Peckham & Peckham, 1892 from Bolivia with first reports of potential ant models for the genus and a novel ant-resembling behavior (Araneae: Salticidae, Simonellini) - Perger, Robert; Rubio, Gonzalo D. (Zootaxa, 2023)
In this work, the results of a survey for species of Fluda Peckham & Peckham, 1892 in primary forest in five Bolivian forest ecoregions are reported. Fluda dauca sp. nov. is described from Southwest Amazon forest and F. thuruampara sp. nov. from Bolivian Yungas forest. Fluda perdita (Peckham & Peckham, 1892) is reported from Bolivia for the first time. Both new species exhibited polymorphic mimicry; dark females of both species resembled the turtle ant Cephalotes pusillus (Klug, 1824) and dark males of F. thuruampara sp. nov. the carpenter ant Camponotus sanctaefidei Dalla Torre, 1892. Orange males and females of F. dauca sp. nov. are likely mimics of Camponotus latangulus Roger, 1863. Males of Fluda may compensate lower mimetic accuracy by the broadened femora I, resembling an ant head in lateral view and ant mandibles when moving the face towards a potential threat. As in other Simonellini, the turnover of Fluda species between the South American superregions suggests that significant shifts in seasonality and related conditions are major factors triggering speciation in the tribe Simonellini.